THE EFFECT OF CRITICAL SPEED EXERCISES ON BLOOD OXYGEN LEVELS AND CONSUMPTION IN YOUNG FOOTBALL PLAYERS - Shamkhi Alfartosy, Dr. Rasool Mohi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The sporting level that we are currently witnessing, and which the majority of countries in the world have reached, must be the result of scientific progress that depends on the results of research and studies conducted in several fields and sciences. The wheel of development will not stop, but studies are still ongoing and continuing to this day for the purpose of obtaining the best. Modern training methods and means that show the best level of achievements and sports performance. Football is one of the group games that requires players to practice it with various physical abilities, especially those that enable them to perform various physical movements and special skills for the game. Critical speed exercises are among the modern training methods used in training at higher levels. The study aimed to prepare exercises in speed training. Critical speed exercises identification of the effects of critical speed. Some exercises are helpful for training purposes physiological variables (the percentage of O2 consumption and the percentage of O2 in the blood). The hypothesis of the current study was that there is an effect of critical speed exercises in developing some physiological variables: the percentage of oxygen consumption and the percentage of oxygen in the blood. The research sample was young players. Karbala Football Club. The researcher used the experimental approach to the research.